An Overview of Smart Attendance System and Communication system - Sumit Kumar Singh; Diksha Kumari; Ankur Singh; Anjali Mathur; Sameer Awasthi (International Journal of Radio Frequency Innovations, 2024)
Our attendance is made more sophisticated and self-controlled by using "the smart attendance system (SAS)," which is the topic of this paper. It has an innovative QR scanner technology that makes the process accurate and simple. The system operates efficiently, saving us time and requiring less labor to maintain attendance. Previous versions of the monitoring system had problems locating students and required a tedious manual attendance method. Thanks to developments in technology, it is now easier to monitor students by integrating automated technologies with the monitoring system. Radio Frequency Identification (RFID) technology is an automated method that enhances the present conventional method of student monitoring Due to the unique ID on each tag, it is simple to identify each tag holder. Furthermore, a Graphical User Interface (GUI) offers an even more effective means of verifying attendance. Consequently, the automatic system created by merging RFID technology and a graphical user interface (GUI) with an attendance system will outperform the conventional approach to student monitoring in terms of efficacy and efficiency. The system provides accurate and efficient attendance management by utilizing a QR scanner. It is a dependable and practical method for managing and monitoring attendance in a range of contexts. In addition to providing precise student information, our QR scanner lowers proxy attendance. This intelligent attendance solution streamlines our administrative tasks, increases overall effectiveness, and provides real-time access to data, analysis, and reporting. In addition to automating the recording of attendance, the intelligent attendance system offers actual insight that supports thoughtful decision-making.
Keywords: Biometric; Database; QR; RFID; scanner recognition; smart attendance system